Metabolites Link Intake of a Healthy Diet to Better Insulin and Glucose Homeostasis in the Microbiome and Insulin Longitudinal Evaluation Study (MILES) - Alexis C Wood; Danielle J Lee; Patricia A Sheridan; Elizabeth T Jensen; Gautam Ramesh; Alain G Bertoni; Stephen S Rich; Yii-Der I Chen; David M Herrington; Jerome I Rotter; Mark O Goodarzi (Current Developments in Nutrition)
Background: Dietary quality has been linked to better glycemic control, but the precise molecular mechanisms giving rise to these associations are not fully understood. Objectives: To examine the association of metabolites associated with the intake of a healthy diet with measures of insulin/glucose homeostasis. Methods: Using cross-sectional data from 295 United States adults, the associations between 3 diet pattern scores and metabolome-wide metabolites were estimated via linear regression models, which controlled for demographic factors and health behaviors. Subsequently, the associations between the diet-related metabolites with 6 measures of glucose/insulin homeostasis were examined in similar models. A Bonferroni correction was applied to control the family-wise error rate at 5%. Results: Fifty-five metabolites were significantly associated with ≥1 diet score (all P < 1.7∗10–5). When these were summed into each of the 3 diet-specific metabolite summary scores, all 3 aggregate measures showed strong associations with 5 out of 6 measures of glucose/insulin homeostasis (P = 9.7∗10–5–4.1∗10–13). Conclusions: Adherence to a priori-defined “healthy diet” is associated with the plasma metabolites that, in turn, are associated with better glycemia. If the associations between replicated in future studies and examined using large-scale longitudinal data, the identified molecules could yield insights into mechanisms by which diet may support glucose and insulin homeostasis.